2014
DOI: 10.1021/ml500144h
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 1,2,4-Triazolopyridines as Inhibitors of Human 11β-Hydroxysteroid Dehydrogenase Type 1 (11β-HSD-1)

Abstract: Small alkyl groups and spirocyclic-aromatic rings directly attached to the left side and right side of the 1,2,4-triazolopyridines (TZP), respectively, were found to be potent and selective inhibitors of human 11β-hydroxysteroid dehydrogenase-type 1 (11β-HSD-1) enzyme. 3-(1-(4-Chlorophenyl)cyclopropyl)-8-cyclopropyl-[1,2,4]triazolo[4,3-a]pyridine (9f) was identified as a potent inhibitor of the 11β-HSD-1 enzyme with reduced Pregnane-X receptor (PXR) transactivation activity. The binding orientation of this TZP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…BMS‐823778 is a potent, selective, competitive and fully reversible inhibitor of human 11β‐HSD1 . Cell free biochemical assays showed that BMS‐823778 was more potent against human 11β‐HSD1 than the animal isoforms, and was 10 000‐fold selective for human 11β‐HSD1 over 11β‐HSD2.…”
Section: Introductionmentioning
confidence: 99%
“…BMS‐823778 is a potent, selective, competitive and fully reversible inhibitor of human 11β‐HSD1 . Cell free biochemical assays showed that BMS‐823778 was more potent against human 11β‐HSD1 than the animal isoforms, and was 10 000‐fold selective for human 11β‐HSD1 over 11β‐HSD2.…”
Section: Introductionmentioning
confidence: 99%
“…11β‐HSD1 knockout mice were found to be resistant to obesity and hyperglycemia. Therefore, it would seem that an inhibitor of 11β‐HSD1 could possibly be an efficacious therapy for the treatment of dysmetabolic syndrome and type 2 diabetes . BMS‐816336, as shown in Figure , represents such an 11β‐HSD1 inhibitor .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would seem that an inhibitor of 11β-HSD1 could possibly be an efficacious therapy for the treatment of dysmetabolic syndrome and type 2 diabetes. [3][4][5] BMS-816336, as shown in Figure 1, represents such an 11β-HSD1 inhibitor. [6][7][8][9] To further the development of BMS-816336, it was necessary to prepare [phenyl-14 C(U)] BMS-816336 for metabolic profiling and stable-isotope labeled BMS-816336 for use as a liquid chromatography/ mass spectrometry (LC/MS) standard.…”
Section: Introductionmentioning
confidence: 99%
“…823778 (Fig. 1A) is a novel, potent, orally administered 11␤HSD-1 inhibitor [6,7]. Data from in vitro studies and early clinical studies indicate that BMS-823778, a prochiral molecule, is metabolized by human liver enzyme Cytochrome P450 2C19 (CYP2C19) to a chiral hydroxy metabolite (BMT-094817- Fig.…”
Section: Introductionmentioning
confidence: 99%